الشبهة وأثرها في درء الحدود - هاني, الجموعي; بريبش, شعيب; _ قويدري, مسعود (University of Eloued-جامعة الوادي, 2015)
نستطيع أن نلخص بحثنا في ثلاثة محاور رئيسة وهي: - الأخذ بالشبهة في درء الحدود مما أجمع عليه فقهاء المذاهب الأربعة، ولم يخالف في ذلك إلا الظاهرية، وقولهم مرجوح لا يعوّل عليه، لأنه لا يتماشى مع مقاصد الشريعة. - الحدود في الإسلام حصن منيع وباب عظيم، يحافظ على كليات الشريعة الخمسة )الدين، العقل، النفس، العرض، المال(. - للشبهة أثر في درء جميع الحدود، فإنها إن ثبتت سقط الحد، لإجماعهم على أن الحدود تدرأ بالشبهات. الترجمة إلى الإنجليزية: We can sum up our research in three main axes. They are Taking with suspicion in warding off restrictive ordinances, that what all the four schools scholars unanimously agreed on, but onlythe " Dhahiria " did not , and their saying is probable so no count .on it, because it is not in line with the purposes of the law In Islam , restrictive ordinances are an impenetrable fortress and a great door, that they maintain the five faculties of law – .) sharia - ( religion, mind, soul, honour, and money The suspicion has its effect in warding off all restrictive ordinances , but as it's proved the ordinance falls to their consensus because of their agreement that the restrictive ..ordinances ward off suspicions
مذكرة ليسانس
Keywords: الشبهة/دراء/ الحدود; Soupçon/conjurer/frontières